The relationship between diurnal cortisol secretion and climacteric-related symptoms. (September 2018) - Katainen, Riina; Kalleinen, Nea; Teperi, Simo; Vahlberg, Tero; Turpeinen, Ursula; Hämäläinen, Esa; Nelimarkka, Lassi; Polo-Kantola, Päivi
Highlights: Previous studies have linked climacteric-related symptoms to cortisol secretion. In this study, only a few associations emerged. Vasomotor and somatic symptoms were associated with lower urinary levels of cortisol. This finding could illustrate a chronic burden caused by the symptoms. Women with more frequent vasomotor symptoms had also a higher cortisol awakening response (CAR). Abstract: Objectives: Chronic stress, also associated with climacteric-related symptoms, may influence cortisol secretion. We studied cortisol metabolism in peri- and postmenopausal women with diverse climacteric-related symptoms. Study design and main outcome measures: The study population was 35 women, aged 45–70 years. Plasma cortisol levels were measured from blood samples collected every 20 min over 24 h. Urinary cortisol was analysed from 24-hour urine collections. Climacteric-related symptoms (vasomotor, sleep, depressive, anxiety, cognitive, sexual, menstrual, and somatic) were evaluated with the Women's Health Questionnaire (WHQ). Associations between cortisol variables (24-hour, night, day, maximum, minimum, morning baseline, cortisol awakening response (CAR), area under the curve, slope, and 24-hour urinary cortisol) and the symptoms were first examined with a correlation analysis. Then, the women were divided into two groups according to their climacteric symptomatology, and differences in cortisol variables between the groups were investigated. Diurnal cortisol curves by symptomatology were also analyzed visually. Results: In the correlation analysis, more frequent vasomotor symptoms were associated with a higher CAR (rs  = 0.37, p = 0.039) and lower 24-hour urinary cortisol excretion (rs = -0.45, p = 0.012), and more frequent depressive symptoms were associated with a higher minimum cortisol level (rs  = 0.33, p = 0.0498). When the women were divided into two groups, women with more frequent vasomotor (p = 0.012) or somatic symptoms (p = 0.021) had a lower 24-hour urinary cortisol excretion than less symptomatic women. Conclusions: Although previous studies have reported associations between climacteric-related symptoms and cortisol secretion, these two factors were not substantially interrelated in our study.